2020
DOI: 10.29252/j.health.11.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Training and Technical Interventions on Improving Safety Culture and Understanding the Risk of Dangerous Situations at Height among Construction Workers

Abstract: Background & objective: Safety training is believed to be one of the pioneering safety measures to improve the safety culture in organizations. The aim of this study was to determine the impact of training and technical interventions on providing a work environment with proper safety culture and understanding the risk of dangerous situations at height among construction workers. Methods: In this interventional study, 394 workers of different job groups in construction companies including impact driver operator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The role of demographic variables Among the demographic variables, a significant relationship was found between education level and safety culture (p = 0.002), education level and job stress (p = 0.006) and education level and job satisfaction (p = 0.011). The study results of Asivandzadeh et al (2020) showed that safety training effectively affects all components of safety culture and workers' empowerment concerning occupational risk perception. Also, a significant improvement in safety culture shows the important role of training interventions and technical interventions as key factors in improving the safety status of workers in the organization.…”
Section: Discussionmentioning
confidence: 98%
“…The role of demographic variables Among the demographic variables, a significant relationship was found between education level and safety culture (p = 0.002), education level and job stress (p = 0.006) and education level and job satisfaction (p = 0.011). The study results of Asivandzadeh et al (2020) showed that safety training effectively affects all components of safety culture and workers' empowerment concerning occupational risk perception. Also, a significant improvement in safety culture shows the important role of training interventions and technical interventions as key factors in improving the safety status of workers in the organization.…”
Section: Discussionmentioning
confidence: 98%
“…This study provides a framework for RP managers' macro-planning to protect workers and prevent occupational accidents. For instance, Asivandzadeh et al [31] showed that safety training significantly impacts all components of safety culture and empowers workers in relation to risk perception of hazardous work situations at height. Shezeen et al [32] verified that workload and accident experience have a positive effect and safety leadership and safety climate have a negative effect on cognitive and emotional risk perception.…”
Section: Literature Reviewmentioning
confidence: 99%